2020
DOI: 10.1002/hyp.13915
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological resilience to forest fire in the subarctic Canadian shield

Abstract: Understanding the role of forest fires on water budgets of subarctic Precambrian Shield catchments is important because of growing evidence that fire activity is increasing. Most research has focused on assessing impacts on individual landscape units, so it is unclear how changes manifest at the catchment scale enough to alter water budgets. The objective of this study was to determine the water budget impact of a forest fire that partially burned a $450 km 2 subarctic Precambrian Shield basin. Water budget co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…While this is said to provide a buffer to climate extremes and variability (Staudinger et al, 2017), precipitation is often substantially higher than dynamic storage capacity (Hayashi, 2020;Hood & Hayashi, 2015) so resistance may be actually relatively low. Spence et al (2020) (Hopp & McDonnell, 2009) but wetter conditions can diminish resistance (Carey et al, 2010).…”
Section: Resiliencementioning
confidence: 99%
See 2 more Smart Citations
“…While this is said to provide a buffer to climate extremes and variability (Staudinger et al, 2017), precipitation is often substantially higher than dynamic storage capacity (Hayashi, 2020;Hood & Hayashi, 2015) so resistance may be actually relatively low. Spence et al (2020) (Hopp & McDonnell, 2009) but wetter conditions can diminish resistance (Carey et al, 2010).…”
Section: Resiliencementioning
confidence: 99%
“…While this is said to provide a buffer to climate extremes and variability (Staudinger et al, 2017), precipitation is often substantially higher than dynamic storage capacity (Hayashi, 2020; Hood & Hayashi, 2015) so resistance may be actually relatively low. Spence et al (2020) identified that antecedent land cover distribution dictated how resistant, and subsequently resilient, permafrost catchments in northern Canada were to forest fire by controlling the amount of area needed to burn to generate a change in hydrological function. This highlights how resistance is a function of the catchment physiography.…”
Section: A Glossary Of Termsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, afforestation influences runoff generation processes (Levia et al, 2020) and regulates soil moisture that provides the catchment template for flooding and hydrological drought (Brodribb et al, 2020) that are expected to be exacerbated under climate change. In addition, afforestation impacts (micro)meteorological conditions and boundary layer energy balances (Hannah et al, 2008), biogeochemical cycling in soils (Levia et al, 2020) and the landscape resilience to fire (Spence et al, 2020) as well as affecting soil habitat conditions, including the spread of soil and plant pathogens (Krause et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…All of these changes have consequences for water table depths and fuel moisture patterns across the landscape, but when and where drought will occur and how the frequency may change is more difficult to predict. Understanding how these changes affect boreal systems, their ecological function, carbon cycling, wildlife habitat, fire regimes, and successional trajectories have all been topics of recent research (Rogers et al, 2015(Rogers et al, , 2020Veraverbeke et al, 2017;Sulla-Menashe et al, 2018;Whitman et al, 2018;Boelman et al, 2019;Marchand et al, 2019;Thompson et al, 2019;Spence et al, 2020;Walker et al, 2020a,b;Baltzer et al, 2021). The effects of a changing climate, in particular drought on peatland wildfire (Thompson et al, 2019), as well as an understanding of peatland-fire interactions (Nelson et al, 2021), have been topics of little research until recently.…”
Section: Introductionmentioning
confidence: 99%